Bayesian networks use in simple maternity problems - Andrade, M.; Ferreira, M. A. M. (Applied Mathematical Sciences, 2014)
The use od DNA profiles in forensic identification problems are common procedure nowadays. Here it is intended to exemplify how to use the analysis of DNA profiles to solve the problem of simple maternity search. For this aim it is necessary to make use of a probabilistic expert system (PES), in the case an object-oriented Bayesian network (OOBN).